Starting from the fundamental trigonometric equation, we have
![\cos^2(\alpha)+\sin^2(\alpha)=1 \iff \sin(\alpha)=\pm√(1-\cos^2(\alpha))](https://img.qammunity.org/2021/formulas/mathematics/high-school/7v1fw4gwa6frvp00996pb2yy9hhfsbn77q.png)
Since
, we know that the angle lies in the third quadrant, where both sine and cosine are negative. So, in this specific case, we have
![\sin(\alpha)=-√(1-\cos^2(\alpha))](https://img.qammunity.org/2021/formulas/mathematics/high-school/31hy1hpkn1lha4iifryrmjfis60c57u307.png)
Plugging the numbers, we have
![\sin(\alpha)=-\sqrt{1-(64)/(289)}=-\sqrt{(225)/(289)}=-(15)/(17)](https://img.qammunity.org/2021/formulas/mathematics/high-school/j0guwpvoiqbgtkrjo1qdc10hf904ta1hpg.png)
Now, just recall that
![\sin(-\alpha)=-\sin(\alpha)](https://img.qammunity.org/2021/formulas/mathematics/high-school/or67mlqh42ivli923n2qhkvwfi28ed7210.png)
to deduce
![\sin(-\alpha)=-\sin(\alpha)=-\left(-(15)/(17)\right)=(15)/(17)](https://img.qammunity.org/2021/formulas/mathematics/high-school/bvxzdt3i5c9k3hmo1iftrbk7dhip59mg24.png)